The Impact of Corporate Governance on the Performance of the Internal Shari Auditor In Islamic Institutions Operating in Jordan - Al-Tahat, Saqer; Quran, Awad (The Arab Journal of Administration, 2022)
The study aimed to identifying the effect of corporate governance on the performance of the internal Shari auditor in the Islamic institutions operating in Jordan. The study used descriptive analytical method to arrive at the results of the analysis of the study data collected by designing a questionnaire for the study to be distributed to the study sample, (40) questionnaires on the sample, and (35) valid questionnaires were retrieved. The study found that there is an impact of the principle of protecting the shareholders’ rights, the principle of equity and equity among the shareholders, the role of stakeholders in corporate governance, and the impact of the principle of disclosure and transparency in corporate governance on the performance of the internal Shari auditor in Islamic institutions.Finally there is an impact of the principle of the responsibilities of the board in corporate governance on the performance of the internal Shari auditor in Islamic institutions. The study recommends that training programs should be conducted for Shari auditor to obtain professional certificates related to forensic auditing and not rely solely on the experience component.